2017
DOI: 10.1007/s00467-017-3640-5
|View full text |Cite
|
Sign up to set email alerts
|

Short courses of daily prednisolone during upper respiratory tract infections reduce relapse frequency in childhood nephrotic syndrome

Abstract: Background -Relapses of childhood nephrotic syndrome (NS) are frequently precipitated by viral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 19 publications
0
42
3
Order By: Relevance
“…to daily administration of prednisolone for 5-7 days prevents the occurrence of relapses. One cross-over trial also supports the use of low-dose daily prednisolone in preventing infection-associated relapses in patients off corticosteroids [59]. Results of the PREDNOS2 trial will clarify the role of these strategies in preventing infectionassociated relapses (ISRCTN10900733).…”
Section: Daily Prednisolone During Infectionsmentioning
confidence: 97%
“…to daily administration of prednisolone for 5-7 days prevents the occurrence of relapses. One cross-over trial also supports the use of low-dose daily prednisolone in preventing infection-associated relapses in patients off corticosteroids [59]. Results of the PREDNOS2 trial will clarify the role of these strategies in preventing infectionassociated relapses (ISRCTN10900733).…”
Section: Daily Prednisolone During Infectionsmentioning
confidence: 97%
“…Several trials suggest that relapses might be reduced if corticosteroids are administered daily for five to seven days at the onset of upper respiratory tract infection in children with FRNS or SDNS who are either not currently taking corticosteroids or taking alternate-day corticosteroids. In the most recent 2017 study by Abeyagunawardena et al, 48 patients with SDNS (but off prednisone for at least three months) were randomized to receive either five days of daily prednisolone at 0.5 mg/kg at the onset of an upper respiratory tract infection or five days of placebo 209 A minority (34.4%) of the treatment group relapsed, whereas 40.6% of the control group experienced a single relapse, and 18.8% had two relapses. These short courses of preemptive corticosteroid treatment may avert the need for longer courses of corticosteroids, therefore reducing toxicity.…”
Section: Key Information Balance Of Benefits and Harmsmentioning
confidence: 99%
“…There is low quality in the evidence for RCTs examining the use of daily and increased dose prednisolone in patients on maintenance therapy with alternate-day prednisolone during viral infections (Table S14 191,[209][210][211][212] ). Relapse and rate of infection-related relapse were the only critical and important outcomes examined in these studies.…”
Section: Quality Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a reduction in relapse rate by a slight, short term increase in the prednisolone dose at the commencement of an URTI in patients with SDNS who were on EOD corticosteroids 13,14,15 . Another study recently demonstrated that a 5 day course of prednisolone prescribed at 0.5mg/kg/day during URTI is capable of reducing the relapse frequency in patients who are off steroids 16 . Based on these findings we make the following recommendations.…”
Section: Prevention Of Relapsesmentioning
confidence: 99%